2004
DOI: 10.1055/s-2004-834910
|View full text |Cite
|
Sign up to set email alerts
|

Friedel-Crafts Cyclization of 1,1-Difluoroalk-1-enes: Synthesis of Benzene-Fused Cyclic Ketones via α-Fluorocarbocations

Abstract: 1,1-Difluoroalk-1-enes bearing a phenyl group at the C-3, -4, or -5 position, readily obtained from 2,2,2-trifluoroethyl p-toluenesulfonate, are treated with FSO 3 H·SbF 5 to undergo FriedelCrafts cyclization in (CF 3 ) 2 CHOH. The cyclization takes place via a-fluorocarbocations, followed by spontaneous hydrolysis of the C-F bond to afford bicyclic ketones including a five, six, or sevenmembered ring in good yield.Fluorine possesses a-carbocation stabilizing effect caused by donation of its unshared electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 2 publications
0
34
0
Order By: Relevance
“…The hydroxyl group would attack the C1 position of 15, giving the four-membered ring intermediate 16, 6 which would ring open to form 17. The ring contraction would take place on its conformer (18) giving trans-5n (path a, Scheme 2). The solvent may have some influence in the stereoselectivity of the electrophilic addition of the iodine(III), explaining the formation of cis-1,3-disubstituted indanes.…”
Section: Mechanism Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydroxyl group would attack the C1 position of 15, giving the four-membered ring intermediate 16, 6 which would ring open to form 17. The ring contraction would take place on its conformer (18) giving trans-5n (path a, Scheme 2). The solvent may have some influence in the stereoselectivity of the electrophilic addition of the iodine(III), explaining the formation of cis-1,3-disubstituted indanes.…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…The behavior of alkene 1n is slightly different to that observed for other substrates. The reaction of 1n with HTIB in CH 3 CN led mainly to indane 5n and ketone 6n 18 in 26 and 23% yield, respectively. The tetralone 6n is formed by migration of the phenyl group.…”
Section: Ring Contractions In Acetonitrilementioning
confidence: 99%
See 1 more Smart Citation
“…[19] The reaction mixture was allowed to warm to room temperature and stirred for 3 h. Chromatographic purification afforded the indenoindene 5 a, with a 6/ 5/5/6 tetracyclic structure, in 63 % yield, together with an 11 % yield of the 2-benzylindanone 6, which originated from D ( Table 1, entry 1). [7] The formation of 5 a confirmed the successful capture of the second carbocation D. [20] The reaction time was prolonged and the reaction temperature was raised in order to improve the yield of 5 a, but in vain (Table 1, 5,6). TLC analysis showed that 1 a was consumed completely within 10 min at 0 8C.…”
Section: Preparation Of Cyclization Precursorsmentioning
confidence: 78%
“…[7] Here, fluorine substituents stabilize a-carbocations by donating their unshared electron pairs into the vacant p orbitals of the cationic centers (+M effect, Figure 1). At the same time, fluorine substituents also act as leaving groups (fluoride ion, F À ), because of their high elecAbstract: In order to synthesize polycyclic aromatic hydrocarbons with nonlinear arrangements (angular PAHs), acid-promoted domino cyclizations of 1,1-difluoroalk-1-enes and 1,1-difluoroalka-1,3-dienes were studied.…”
Section: Introductionmentioning
confidence: 98%